2021
DOI: 10.7759/cureus.19347
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Male Sexual Activity Versus Alpha-Blockers in the Expulsion of Distal Ureteric Stones: A Systematic Review and Meta-Analysis

Abstract: Globally, the prevalence of urolithiasis is increasing, with limited effective treatment options. Though debate exists within the literature, the use of medical expulsive therapy (MET) for distal ureteric stones in the form of alpha-blockers is commonplace. Alpha-blockers work via the inhibition of norepinephrine, resulting in a small degree of distal ureteric relaxation. Nitric oxide (NO), the main neurotransmitter involved in penile erection, causes smooth muscle relaxation of the distal ureter. It is hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, tamsulosin may not be a favorable choice for men who wish to avoid medication and its associated side effects, such as retrograde ejaculation (experienced by 8–18% of users), as well as orthostatic hypotension, headache, dizziness, and diarrhea. Prior use of tamsulosin can also complicate cataract surgery by causing floppy iris syndrome 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, tamsulosin may not be a favorable choice for men who wish to avoid medication and its associated side effects, such as retrograde ejaculation (experienced by 8–18% of users), as well as orthostatic hypotension, headache, dizziness, and diarrhea. Prior use of tamsulosin can also complicate cataract surgery by causing floppy iris syndrome 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Among all urinary stones, ~20% can be located in the ureter, while 70% are found in the distal ureteric segment 2 , 3 . The escalating burden of kidney stone disease has substantial costs for healthcare systems, and the disease also has a negative impact on the patient’s quality of life 4 . There is a 50% chance of distal UTS spontaneously passing via conservative treatment within a 6-week period 3 .…”
Section: Introductionmentioning
confidence: 99%
“…However substantial amount of literature is lacking on this new modality of management. In one systematic metanalysis review by Chaolo HC Juman et.al, found that increased sexual activity (thrice a week) is comparable to a-blocker in expulsion of distal ureteral stone size up to 10 mm especially those patients who are reluctant to pharmacological treatment 10 . In an another randomized controlled trial by Liw, Mao-Y et.al, concluded that at least 3 sexual intercourse per week after SWL can effectively increase the stone passage rate, decrease the formation of steinstrasse and the relief of renal colic 11 .…”
Section: Discussionmentioning
confidence: 99%